ROAD MAINTENANCE STRATEGY OPTIMIZATION USING MULTI OBJECTIVE OPTIMIZATION ALGORITHM (CASE STUDY: DINAS BINA MARGA DAN PENATAAN RUANG PROVINSI JAWA BARAT) - Dimas Priambodo, Ignatius
Road has become an important part of supporting human life, such as in the economic, socio-cultural, security, and to the prosperity of the community. Road maintenance must be carried out continuously so that the road can provide optimal benefits. Unfortunately, road maintenance activities in Indonesia cannot run optimally. The limited road maintenance resources available urges the determination of the optimal road management strategy by considering various aspects. However, the strategy for road maintenance that has been done so far is still manual. On the other hand, road maintenance activities are needed to guarantee a sense of comfort and safety to road users. Research on determining road management strategies has been carried out in recent years. However, these studies are limited to the optimization of two objective variables, such minimization of cost over planning time to preserve road serviceability and maximization of road surface conditions. Meanwhile, there are other variables that could be considered in determining the optimal road management strategy, such as disaster-prone data. In addition, the budget limit available each year has not been considered in the existing research. This study recommends a metaheuristic method for multi-objective optimization that can support road maintenance activities by providing optimal road handling strategies from limited available resources. This study also presents a prototype that applies the method to support the optimal problem solution and results of the optimal road handling strategy. The results showed that NSGA-III was able to provide fast, precise, and efficient optimization, compared to other optimization methods. In addition, there is still room to improve the performance of the NSGAIII to be even better.